Molecular Analysis of Carbapenem and Aminoglycoside Resistance Genes in Carbapenem-Resistant Pseudomonas aeruginosa Clinical Strains: A Challenge for Tertiary Care Hospitals - Aamir Jamal Gondal; Nakhshab Choudhry; Ammara Niaz; Nighat Yasmin (MDPI AG, 2024)
Carbapenem-resistant Pseudomonas aeruginosa (P. aeruginosa) strains have become a global threat due to their remarkable capability to survive and disseminate successfully by the acquisition of resistance genes. As a result, the treatment strategies have been severely compromised. Due to the insufficient available data regarding P. aeruginosa resistance from Pakistan, we aimed to investigate the resistance mechanisms of 249 P. aeruginosa strains by antimicrobial susceptibility testing, polymerase chain reaction for the detection of carbapenemases, aminoglycoside resistance genes, extended-spectrum beta-lactamases (ESBLs), sequence typing and plasmid typing. Furthermore, we tested silver nanoparticles (AgNPs) to evaluate their in vitro sensitivity against antimicrobial-resistant P. aeruginosa strains. We observed higher resistance against antimicrobials in the general surgery ward, general medicine ward and wound samples. Phenotypic carbapenemase-producer strains comprised 80.7% (201/249) with 89.0% (179/201) demonstrating genes encoding carbapenemases: blaNDM-1 (32.96%), blaOXA48 (37.43%), blaIMP (7.26%), blaVIM (5.03%), blaKPC-2 (1.12%), blaNDM-1/blaOXA48 (13.97%), blaOXA-48/blaVIM (1.68%) and blaVIM/blaIMP (0.56%). Aminoglycoside-modifying enzyme genes and 16S rRNA methylase variants were detected in 43.8% (109/249) strains: aac(6')-lb (12.8%), aac(3)-lla (12.0%), rmtB (21.1%), rmtC (11.0%), armA (12.8%), rmtD (4.6%), rmtF (6.4%), rmtB/aac(3)-lla (8.2%), rmtB/aac(6')-lla (7.3%) and rmtB/armA (3.6%). In total, 43.0% (77/179) of the strains coharbored carbapenemases and aminoglycoside resistance genes with 83.1% resistant to at least 1 agent in 3 or more classes and 16.9% resistant to every class of antimicrobials tested. Thirteen sequence types (STs) were identified: ST235, ST277, ST234, ST170, ST381, ST175, ST1455, ST1963, ST313, ST207, ST664, ST357 and ST348. Plasmid replicon types IncFI, IncFII, IncA/C, IncL/M, IncN, IncX, IncR and IncFIIK and MOB types F11, F12, H121, P131 and P3 were detected. Meropenem/AgNPs and Amikacin/AgNPs showed enhanced antibacterial activity. We reported the coexistence of carbapenemases and aminoglycoside resistance genes among carbapenem-resistant P. aeruginosa with diverse clonal lineages from Pakistan. Furthermore, we highlighted AgNP's potential role in handling future antimicrobial resistance concerns.